2007
DOI: 10.1002/cpp.553
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study into the use of the five factor model of personality with individuals with intellectual disabilities

Abstract: This paper is an exploratory study in two parts into the adaptation of the NEO-PI-R for use with individuals with intellectual disabilities (IDs). Study 1 was concerned with the simplification and reliability of questions to retain the meaning of the original. Eight participants completed both the original and the adapted versions, showing a very high consistency between versions. In Study 2, the adapted questionnaire was administered to an outpatient group of 40 people with ID. A rater version of each was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Furthermore, until relatively recently, there was a reluctance to diagnose an already stigmatized group with a further pejorative label such as PD (Lindsay et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, until relatively recently, there was a reluctance to diagnose an already stigmatized group with a further pejorative label such as PD (Lindsay et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the disparity between work that has been completed in the field of ID and the extensive and varied research completed on personality assessment in the mainstream population, there is clearly a need for information, which will both help the integration of these two systems and allow clinicians and researchers to review the relevance of work on mainstream personality systems for clients with ID. Lindsay, Rzepecka and Law (2007) presented a study in which they investigated the utility of the FFM in this client group. They found that a questionnaire that assessed FFM factors could be adapted successfully for people with ID.…”
Section: Introductionmentioning
confidence: 99%
“…Ovi procesi imaju svoje implikacije i u pogledu uključivanja osoba sa intelektualnim teškoćama u proces naučnog ispitivanja različitih psihičkih i drugih fenomena. U tom smislu, primetni su pokušaji usmereni na ispitivanje kompetentnosti i pozitivnih aspekata ličnosti osoba sa intelektualnim teškoćama, kao i primene instrumenata za procenu ličnosti u celini, poput NEO PI R-a, operacionalizacije petofaktorskog modela ličnosti (Petrović, 2008;Lindsay, Rzepecka, Law, 2007). Pored toga, akcenat polako počinje da se stavlja na skale procene i samoprocene osoba sa intelektualnim teškoćama, mada se i dalje instrumenti prevashodno razvijaju za potrebe (samo)procene različitih mentalnih teškoća psihijatrijskog tipa.…”
unclassified